Effects of a 3-month dietary intervention with a lacto-ovo-vegetarian diet on vitamin B12 levels in a group of omnivores: results from the CARDIVEG (Cardiovascular Prevention with Vegetarian Diet) study. Issue 7 (26th December 2018) - Dinu, M.; Pagliai, G.; Cesari, F.; Giusti, B.; Gori, A. M.; Marcucci, R.; Casini, A.; Sofi, F.
Abstract: Previous studies have suggested that vegetarianism can result in a reduction of vitamin B12 circulating levels. The aim of the present study was to investigate the effects of a 3-month dietary intervention with a lacto-ovo-vegetarian diet (VD) on the levels of circulating vitamin B12 in a group of omnivores. We analysed fifty-four omnivorous subjects who followed a VD as a first dietary intervention within the CARDIVEG (Cardiovascular Prevention with Vegetarian Diet) study, a dietary intervention study. VD resulted in a significant reduction ( P <0·001) of 51·2 % of vitamin B12 intake and in a significant reduction ( P =0·005) of 6·2 % of the circulating levels of vitamin B12 (–24·5 pg/ml). Changes in vitamin B12 intake were significantly correlated with changes in circulating levels of vitamin B12 ( R 0·61, P <0·001). Subgroup analyses showed that reduction in circulating vitamin B12 levels was more evident in participants who were younger, overweight, non-smokers and had hypercholesterolaemia. A logistic regression analysis showed that a reduction in vitamin B12 intake greater than the first quartile of the delta changes obtained in the study population (–28·5 %) conferred a significantly higher risk of experiencing a decrease in circulating vitamin B12 levels (OR 10·1; 95 % CI 1·3, 76·1). In conclusion, a 3-month VD period determined a significant reduction in circulating levels of vitamin B12, being significantly correlated with the reduction in vitamin B12 intake. Although a well-planned VD can provide adequate nutrition across all life stages, special care must be taken to ensure adequate vitamin B12 intake and to help prevent deficiency.